2022
DOI: 10.1038/s41598-022-06189-5
|View full text |Cite
|
Sign up to set email alerts
|

Aged related human skin microbiome and mycobiome in Korean women

Abstract: We examined differences in the skin microbiome of two separate age groups to find key microbial and skin physiological indicators associated with aging. We recruited healthy Korean women 19–28 years old (Y-group) and 60–63 years old (O-group) and evaluated their cheek and forehead skin microbiome, including bacteria and fungi. The microbiome was significantly different by age group, with bacterial and fungal communities displaying higher alpha-diversity in the O-group than in the Y-group. We identified amplico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 33 publications
(37 reference statements)
12
33
0
Order By: Relevance
“…As intrinsic ageing underpins both types of ageing, these results suggest that microbial diversity is highly dictated by intrinsic ageing mechanisms. This has been corroborated in other studies in women, with the within-sample microbial diversity of aged skin being significantly higher than that in young adult skin and most significant in sun-protected sites [ 9 , 104 , 108 , 141 ]. Overall abundance of bacteria increases with age, but this is not directly proportional as certain bacteria become more dominant (e.g., Corynebacterium ) while others decline in number (e.g., Cutibacterium and Lactobacillus [ 9 , 104 , 108 , 141 ]) in a site-independent manner.…”
Section: Skin Ageing and The Microbiomesupporting
confidence: 84%
See 3 more Smart Citations
“…As intrinsic ageing underpins both types of ageing, these results suggest that microbial diversity is highly dictated by intrinsic ageing mechanisms. This has been corroborated in other studies in women, with the within-sample microbial diversity of aged skin being significantly higher than that in young adult skin and most significant in sun-protected sites [ 9 , 104 , 108 , 141 ]. Overall abundance of bacteria increases with age, but this is not directly proportional as certain bacteria become more dominant (e.g., Corynebacterium ) while others decline in number (e.g., Cutibacterium and Lactobacillus [ 9 , 104 , 108 , 141 ]) in a site-independent manner.…”
Section: Skin Ageing and The Microbiomesupporting
confidence: 84%
“…This has been corroborated in other studies in women, with the within-sample microbial diversity of aged skin being significantly higher than that in young adult skin and most significant in sun-protected sites [ 9 , 104 , 108 , 141 ]. Overall abundance of bacteria increases with age, but this is not directly proportional as certain bacteria become more dominant (e.g., Corynebacterium ) while others decline in number (e.g., Cutibacterium and Lactobacillus [ 9 , 104 , 108 , 141 ]) in a site-independent manner. Certain genera are also altered by body site, such as higher abundance of Streptococcus and lower abundance of Staphylococcus on the buttocks [ 9 ].…”
Section: Skin Ageing and The Microbiomesupporting
confidence: 84%
See 2 more Smart Citations
“…On one hand, confounding factors such as sex, ethnicity, geography, and health condition can all affect skin microbiome 18 , which increase data dimensionality and decrease statistical power 7 . On the other hand, while previous investigations revealed aging-related skin microbiome changes at phylum-to genus-resolution 11,[14][15][16][17][18] , studies by our group and others have shown that the aging-related diversity of the skin microbiome is often manifested at species-, strain-, or genelevel 7 . Moreover, such high-resolution diversity has potential health implications.…”
Section: Introductionmentioning
confidence: 60%